(The Utilization of Sodium Chloride (NaCI) and Phosphoric Acid (H3PO4) on Degguming Process to Refine Crude Patin Oil (Pangasius sp.) - Lestari, Nami; Susanty, Arba; -, Kurniawaty (Warta Industri Hasil Pertanian, 2008)
The oil paten fish (pangasius sp.) is a by product of paten nugget processing. It contains fatty acid and other nutriens compounds utilized in food and pharmaceutical industries. Refining is needed to utilize the raw oil fish of patin. The aim of this research was to find out a refining technology of patin oil fish by trretment of degumming. The research used two trreatment of degumming using 2.5% of salt (NaCI) an 2.0% of phosphate acid (H2PO4). Both were neutralized with Sodium Hydroxide (NaOH) and bleached with actived carbon. The reslt showed that the more accurate technique to refine oil fish of patin was by degumming process using 2.5% of salt, neutralization with NaOH and bleaching with actived carbon. The testing of pure oil fish of patin resulted in a metting to the requirement of food and pharmaceutical industry